Respuestas
Respuesta dada por:
0
lado izquierdo
![{x}^{4 } - 5 {x}^{2} + x {x}^{4 } - 5 {x}^{2} + x](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B4+%7D+-+5+%7Bx%7D%5E%7B2%7D+%2B+x)
=
lado derecho
![- 5 {x}^{2} + 10x + {x}^{4} + 18 - 5 {x}^{2} + 10x + {x}^{4} + 18](https://tex.z-dn.net/?f=+-+5+%7Bx%7D%5E%7B2%7D+%2B+10x+%2B+%7Bx%7D%5E%7B4%7D+%2B+18)
después
![- 5 {x}^{2} + 10x + {x}^{4} + 18 - {x}^{4} + 5 {x}^{2} - x - 5 {x}^{2} + 10x + {x}^{4} + 18 - {x}^{4} + 5 {x}^{2} - x](https://tex.z-dn.net/?f=+-+5+%7Bx%7D%5E%7B2%7D+%2B+10x+%2B+%7Bx%7D%5E%7B4%7D+%2B+18+-+%7Bx%7D%5E%7B4%7D+%2B+5+%7Bx%7D%5E%7B2%7D+-+x)
=
9x + 18 = 0
9x = 18
x = 18/9
x=2
=
lado derecho
después
=
9x + 18 = 0
9x = 18
x = 18/9
x=2
Respuesta dada por:
0
Respuesta:
x²(x² - 5) + x = - 5(x² - 2x) + x⁴ + 18
x⁴ - 5x² + x = - 5x² + 10x + x⁴ + 18
x = 10x + 18
- 18 = 10x - x
- 18 = 9x
- 18 / 9 = x
- 2 = x
x = - 2
x²(x² - 5) + x = - 5(x² - 2x) + x⁴ + 18
x⁴ - 5x² + x = - 5x² + 10x + x⁴ + 18
x = 10x + 18
- 18 = 10x - x
- 18 = 9x
- 18 / 9 = x
- 2 = x
x = - 2
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años